Human Eosinophil Leukocytes Express Protein Disulfide Isomerase in Secretory Granules and Vesicles: Ultrastructural Studies. (June 2014) - Dias, Felipe F.; Amaral, Kátia B.; Carmo, Lívia A. S.; Shamri, Revital; Dvorak, Ann M.; Weller, Peter F.; Melo, Rossana C. N.
Protein disulfide isomerase (PDI) has fundamental roles in the oxidative folding of proteins in the endoplasmic reticulum (ER) of eukaryotic cells. The study of this molecule has been attracting considerable attention due to its association with other cell functions and human diseases. In leukocytes, such as neutrophils, PDI is involved with cell adhesion, signaling and inflammation. However, the expression of PDI in other leukocytes, such as eosinophils, important cells in inflammatory, allergic and immunomodulatory responses, remains to be defined. Here we used different approaches to investigate PDI expression within human eosinophils. Western blotting and flow cytometry demonstrated high PDI expression in both unstimulated and CCL11/eotaxin-1-stimulated eosinophils, with similar levels in both conditions. By using an immunogold electron microscopy technique that combines better epitope preservation and secondary Fab-fragments of antibodies linked to 1.4-nm gold particles for optimal access to microdomains, we identified different intracellular sites for PDI. In addition to predictable strong PDI labeling at the nuclear envelope, other unanticipated sites, such as secretory granules, lipid bodies and vesicles, including large transport vesicles (eosinophil sombrero vesicles), were also labeled. Thus, we provide the first identification of PDI in human eosinophils, suggesting that this molecule may have additional/specific functions in these leukocytes.